Comparative Analysis of Tax Administration between Indonesia and New Zealand - Kumalasari, Kartika Putri; Haliza, Ananda Nur; Alfandia, Nurlita Sukma; Agusti, Rosalita Rachma (Profit: Jurnal Adminsitrasi Bisnis, 2023)
This study focuses on a comparative analysis of institutional position, taxpayer registration, and tax reporting between Indonesia and New Zealand. This study aims to see the potential of the New Zealand tax administration that can be adapted and adopted in Indonesia to improve administration so that it can encourage taxpayer compliance behavior. This research is descriptive qualitative research and data collection through literature studies. The analytical method used is the content analysis model. The results of this study indicate that there is still room available to make improvements in tax administration, including the Directorate General of Taxes, can provide social program assistance for taxpayers who have a Taxpayer Identification Number, increasing the role of the Directorate General of Taxes not only as a tax collection and management agency but also managing social policy programs, and changing the institution of the former Directorate General of Taxes single directorate within the ministry of finance or economy become semi-autonomous revenue authorities. The results of this study can be used as a consideration for the Directorate General of Taxes to implement in Indonesia to improve tax administration that can encourage compliant behavior.